Commodity Markets Outlook, Ocotober 2016 : OPEC in Historical Context - World Bank Group (World Bank, Washington, DC, 2016)
Most commodity prices continued to rise in the third quarter from their lows in early 2016. Crude oil prices are forecast to rise to $55 per barrel in 2017 from an average of $43/bbl this year as the market continues to rebalance and OPEC is likely to limit output. Metals prices are projected to rise more sharply in 2017 than forecast in July, as a result of faster-than-expected mine closures. Agricultural commodities prices are anticipated to rise slightly in 2017 after a minimal decline this year but with wide variations in the outlook for different commodities depending on supply conditions. This issue of the Commodity Markets Outlook analyzes OPEC’s recent decision to limit output by examining earlier commodity agreements and assessing the implications of changing market forces over the past decades. It concludes that commodity agreements have limited ability to influence global prices over extended periods of time and eventually collapse, often with unintended consequences. The ability of OPEC, the only surviving commodity organization seeking to influence markets, will be tested in the presence of unconventional oil suppliers, notably the U.S. shale oil industry.